Impact of different straw treatment methods on agricultural production efficiency: An empirical evidence of Jiangsu Province of China - Huan Chen; Ehsan Elahi; Xinyuan Lei (Frontiers in Environmental Science, 2022)
Using county-level panel data collected from Jiangsu Province of China, this study applies the Super-SBM model to investigate the impact of straw retention subsidy and straw burning on agricultural production efficiency. The results found that the agricultural efficiency measurement system with cultivated land quality is more realistic. Agricultural development in the southern part of Jiangsu Province is at the expense of the environment. Straw burning in the open field can significantly improve the efficiency of traditional agricultural production. Moreover, it is found that the straw retention subsidy cannot improve efficiency directly, but it can inhibit straw burning from technical substitution and policy effects. The subsidy may work better when it is applied to local conditions. Moreover, to improve technical efficiency, it is suggested that government should pay attention to both operation training and supervision systems when promoting straw returning technology. In the long run, it is imperative to optimize the comprehensive utilization structure of straws and broaden the range of straw utilization. The findings of the study have broad implications for other agrarian regions with similar issues.